Resposta :
Resposta:
. 2x² + 2y² + 4
Explicação passo a passo:
.
. (x² - 3xy + y² - 1) - (- x² - 5 - y² - 3xy) =
. x² - 3xy + y² - 1 + x² + 5 + y² + 3xy =
. x² + x² - 3xy + 3xy + y² + y² - 1 + 5 =
. 2x² + 2y² + 4
.
(Espero ter colaborado)
Resposta:
[tex]2x {}^{2} + 2y {}^{2} + 4[/tex]
Explicação passo-a-passo:
[tex](x {}^{2} - 3xy + y {}^{2} - 1) - ( - x {}^{2} - 5 - y {}^{2} - 3xy) = [/tex]
[tex]x {}^{2} = 3xy + y {}^{2} - 1 + x {}^{2} + 5 + y {}^{2} + 3xy = [/tex]
[tex]2x {}^{2} + 2y {}^{2} + 4[/tex]